ORGANIZATION OF ACCOUNTING OF FOREIGN ECONOMIC ACTIVITIES IN THE CONDITIONS OF FULL-SCALE WAR - PANASYUK, Valentyna; TKACHUK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the conditions of a full-scale war, one of the key issues is conducting effective foreign economic activity, namely, meeting the needs of society and the army during the war. With the beginning of military aggression, when the question arose of quickly supplying the army with military equipment, food, and tools, the main shortcomings of the country's current foreign economic policy became apparent. The most famous cases are the processes of customs clearance and import of military goods from abroad.The work highlights two main groups of problems that our state faced when conducting foreign economic activities during the war: problems of foreign exchange accounting and problems of minimizing foreign exchange risks.The main problems of foreign economic activity accounting include: organization of accounting in this area, taxation of operations of foreign economic activity; accounting problems in accordance with National Standards. Such problems can cause incorrect documentation of cargo, errors in taxation, etc. The consequences of such mistakes can be administrative penalties in the form of fines, the imposition of sanctions, which may cause financial losses and reduce the image of the enterprise.The main new risks that appeared with the beginning of a full-scale war are: risks of non-fulfillment of contracts, logistical risks, risks of non-fulfillment of delivery dates, risks of non-fulfillment of contract payments. As a result, costs arise from non-compliance with the terms of the contract and financial sanctions are imposed, provided for by the terms of this contract.Each of these groups requires detailed study to avoid negative results as a result of conducting ED. The work highlights and explains the essence of import-export operations. The main group of problems that have a significant impact on the organization of accounting for foreign economic activity in Ukraine has been identified. An analysis of purchases and sales was carried out, based on which the influence of certain problems on the results of the country's foreign economic activity was reflected.
Keywords: accounting; foreign economic activity; import; export; import duty; martial law; international trade